2008
DOI: 10.1002/glia.20771
|View full text |Cite
|
Sign up to set email alerts
|

The glycoprotein fibulin‐3 regulates morphology and motility of olfactory ensheathing cells in vitro

Abstract: The primary olfactory pathway in adult mammals has retained a remarkable potential for self-repair. A specialized glial cell within the olfactory nerve, called olfactory ensheathing cell (OEC), and their associated extracellular matrix are thought to play an important role during regenerative events in this system. To gain insight into novel molecules that could mediate the OEC-supported growth of axons within the olfactory nerve, gene expression profiling experiments were conducted which revealed high express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 91 publications
4
34
0
1
Order By: Relevance
“…Only 4 factors have been identified to functionally modulate OEC migration, 3 of which are known modulators of axonal extension (glial derived neurotrophic factor, GDNF, Nogo-66 and Slit-2) [46,47,48], and 1 extracellular matrix protein, fibulin 3 [49]. Because OECs are regarded as such important regulators of axon growth and guidance, and particularly since we have recently shown that an increased OEC migration rate leads to enhanced axon growth [22], a clear characterisation of how migration of OECs is regulated is also interesting from a clinical perspective.…”
Section: Regulation Of Oec Migration At a Molecular Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 4 factors have been identified to functionally modulate OEC migration, 3 of which are known modulators of axonal extension (glial derived neurotrophic factor, GDNF, Nogo-66 and Slit-2) [46,47,48], and 1 extracellular matrix protein, fibulin 3 [49]. Because OECs are regarded as such important regulators of axon growth and guidance, and particularly since we have recently shown that an increased OEC migration rate leads to enhanced axon growth [22], a clear characterisation of how migration of OECs is regulated is also interesting from a clinical perspective.…”
Section: Regulation Of Oec Migration At a Molecular Levelmentioning
confidence: 99%
“…OEC processes form conduits [61] that express a range of extracellular matrix proteins of which many are involved in cell adhesion [15,32,53]. One extracellular matrix protein has been shown to directly regulate the migration of OECs: the Ca 2+ -binding glycoprotein fibulin 3 [49]. Viral-mediated overexpression of fibulin 3 in OECs inhibited OEC migration and instead promoted OEC proliferation.…”
Section: Regulation Of Oec Migration At a Molecular Levelmentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that in injured spinal cord, rat and human OECs migrate for shorter distances, in both rostral and caudal directions, compared to non-injured spinal cords [20]. At the molecular level, GDNF [21], Slit-2 [22,23], NogoA [24,25] and fibulin-3 [26] have been demonstrated to regulate OEC migration. In fact, we and others have demonstrated that the OEC migratory potential is largely impaired by myelin [24,25,27,28] and that this inhibition may be partially overcome by treatment with NEP1-40 peptide [24] or antibodies against the myelin receptor Nogo receptor [25].…”
Section: Introductionmentioning
confidence: 99%
“…5F). proliferation has recently been carried out on over glass surfaces with artificially generated gradients (Yan et al, 2003;Cao et al, 2006;Vukovic et al, 2009;Huang et al, 2011), in collagen scaffolds (Wang et al, 2006;Mollers et al, 2009), in nanofibers (Shen et al, 2010) and in biomaterial-coated substrates (Martin-Lopez et al, 2010b;Martin-Lopez et al, 2010a).…”
mentioning
confidence: 99%